2004
DOI: 10.1371/journal.pbio.0020280
|View full text |Cite
|
Sign up to set email alerts
|

Sterol-Derived Hormone(s) Controls Entry into Diapause in Caenorhabditis elegans by Consecutive Activation of DAF-12 and DAF-16

Abstract: Upon starvation or overcrowding, Caenorhabditis elegans interrupts its reproductive cycle and forms a specialised larva called dauer (enduring). This process is regulated by TGF-β and insulin-signalling pathways and is connected with the control of life span through the insulin pathway components DAF-2 and DAF-16. We found that replacing cholesterol with its methylated metabolite lophenol induced worms to form dauer larvae in the presence of food and low population density. Our data indicate that methylated st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
198
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(203 citation statements)
references
References 45 publications
3
198
0
2
Order By: Relevance
“…Second, DDtps could not suppress the induction of wild-type dauers on substitution of cholesterol by lophenol. As previously shown, DA cannot be produced when lophenol is the only dietary sterol because cholesterol, the precursor for DA synthesis, is absent 25 . DDtps formed dauer larvae on lophenol and this process was not decreased by starvation (Fig.…”
Section: Trehalose-deficient Mutants Exhibit Reduced Dauer Formationmentioning
confidence: 92%
See 1 more Smart Citation
“…Second, DDtps could not suppress the induction of wild-type dauers on substitution of cholesterol by lophenol. As previously shown, DA cannot be produced when lophenol is the only dietary sterol because cholesterol, the precursor for DA synthesis, is absent 25 . DDtps formed dauer larvae on lophenol and this process was not decreased by starvation (Fig.…”
Section: Trehalose-deficient Mutants Exhibit Reduced Dauer Formationmentioning
confidence: 92%
“…24). Conversely, activation of DAF-12 caused by mutation of daf-9 or substitution of the dietary cholesterol with lophenol also induces the formation of arrested dauer-like larvae in daf-16 loss-of-function mutants 25,35 .…”
Section: Availability Of Cytosolic Nadph Determines Dauer Formationmentioning
confidence: 99%
“…Identified pathways regulating this decision include insulin/ IGF-1, TGF-b and cyclic GMP signalling. These signal transduction pathways converge on DAF-9, a cytochrome P450 steroid hydroxylase which is postulated to produce a cholestrol-derived hormone (Gerish and Antebi, 2004;Matyash et al, 2004). The target of this putative hormone is the nuclear hormone receptor DAF-12.…”
Section: Introductionmentioning
confidence: 99%
“…Reduction of SAMS-1 and PMT-2 should reduce methylation levels of their substrates in worms grown in CS. It was reported that cholesterol depletion caused accumulation of methylated sterols (Matyash et al, 2004). This finding suggests that SAMS-1 and PMT-2 are not involved in sterol methylation because their levels were decreased in CS.…”
Section: Discussionmentioning
confidence: 90%